Penilaian Kinerja Aparatur Sipil Negara Secara Elektronik (E-Sikap) Pada Dinas Pekerjaan Umum, Penataan Ruang, Perumahan, Kawasan Permukiman Dan Pertanahan (PUPRPKPP) Provinsi Riau - Prihati; Slamet Makharip (Bahasa Indonesia, 2021)
Employee performance appraisal is an important thing that must be done as a means to obtain accurate data including the results of employee performance achievements. The data obtained from a performance appraisal system will greatly assist the leadership in determining further steps related to careers and employee development in the future. The purpose of this study was to find out how the performance appraisal was carried out, and wanted to see whether the apparatus performance appraisal system based on the electronic SKP (e-SIKAP) application that was applied was reliable, and could be used as a basis for evaluating employee performance, especially at the Public Works, Spatial Planning Service. , Housing, Settlement and Land Areas (PUPRPKPP) Riau Province.The method used in this study is a qualitative approach, where the research carried out describes the actual phenomenon of events in the field. Data collection techniques are direct observation, interviews, and documentation related to research. Based on the results of the study, it can be concluded that: ASN performance assessment at the Riau Province PUPRPKPP Service using the e-SIKAP electronic application, which aims to improve ASN performance and organizational performance, as well as payment terms for Additional Employee Allowances. The assessment carried out includes an assessment of employee work targets (SKP) for a period of one year, and an assessment of the achievement of monthly work targets which are assessed every month for a period of one year